Dinosaurs - Benton, Michael (Kingfisher London, 1994)
Focusing on dinosaurs and other prehistoric animals, this is part of a 12-volume encyclopaedia which aims to reflect the concerns of the National Curriculum. The book examines what prehistoric creatures were like, where they lived, why they disappeared, and how they are rediscovered.